MAPS OF SCIENCE: VISUAL PRACTICES OF SCIENCE CLASSIFICATION - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2015)
Article deals with the analysis of various maps of science. Map is defined as visual means, such as atlases, diagrams, tables or trees, which are applied in classification and arrangement of different sciences and scientific disciplines. The article aims at the analysis of the visual means practiced in classifications of sciences, critical evaluation of their assumptions, principles of mapmaking, and their informativity. Approaches of philosophy and sociology of science are supported by geographic and cartographic methodologies that enable to investigate maps as more or less accurate representations of scientific field, which increases their convincing potential in power-related games.
Keywords: classification of sciences; tree of knowledge; map of science; philosophy of science; sociology of science; knowledge and power